M. V. Ostrogradsky As Probabilist - Seneta, E. М. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We review the writings on probabilistic topics of M. V. Ostrogradsky (1801–1862) in the bicentenary year of his birth from a standpoint different from the sesquicentenary article of Gnedenko. Ostrogradsky's statistical technology follows closely that of Laplace's Théorie Analytique des Probabilités in its use of the Bayes theorem together with the principle of insufficient reason. He makes more precise or modifies certain of Laplace's application-oriented conclusions. The more striking results relate to sampling for attributes without replacement in a finite population and to the probability of error by a panel of judges, anticipating Poisson.